2021
DOI: 10.1021/acsestengg.1c00246
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Response of the Reductive Reactivity of Zerovalent Iron toward the Coexistence of Natural Organic Matter

Abstract: Although the existence of ubiquitous natural organic matter (NOM) exerts significant effects on the performance of zerovalent iron (ZVI), size-dependent response of the reactivity of ZVI toward NOM under both aerobic and anaerobic conditions has not been considered. In this study, the oxic removal and anoxic removal of the pollutant diatrizoate (DTA) by mechanochemically prepared ZVI of varying sizes in the presence of humic acid (HA), a typical NOM, were investigated comparatively. When oxygen was present, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…4d), 44 implying the formation of the Hg–NOM complexes through the complexation between Hg and –COOH and/or –OH groups on the NOM molecules. 45–47 Additionally, the particle size and ζ potential of MoS 2 remained unaffected by the addition of NOM with concentration up to 100 mg L −1 (Fig. S14†).…”
Section: Resultsmentioning
confidence: 98%
“…4d), 44 implying the formation of the Hg–NOM complexes through the complexation between Hg and –COOH and/or –OH groups on the NOM molecules. 45–47 Additionally, the particle size and ζ potential of MoS 2 remained unaffected by the addition of NOM with concentration up to 100 mg L −1 (Fig. S14†).…”
Section: Resultsmentioning
confidence: 98%
“…For example, Cu/ZnO/Al 2 O 3 catalyst had retained 80% catalytic activity in the presence of 2% sulfur but Cu/Al 2 O 3 catalyst was completely deactivated with only 0.2% sulfur 35 , 64 . Chen et al 65 reported higher HA adsorption on nZVI than micro-ZVI surface which resulted in lesser H * formation on the nZVI and, thus, lesser contaminant degradation. Though extensive work has been published on the effects of groundwater constituents on various copper catalysts (mostly supported catalysts), no study has investigated their effects on the catalytic efficiency of nCu 0 synthesized by borohydride reduction method.…”
Section: Resultsmentioning
confidence: 99%
“…NZVI, ferrous ions, and active H* are found to be the primary reductive species in the ZVI-based reduction process. , Therefore, it is necessary to examine their contribution to Cr­(VI) reduction in the Fe(0)/Fe 3 C@MesoC system. 1,10-Phenanthroline and tert -butyl alcohol were used as scavengers to quench the surface ferrous ions and H*, respectively. As depicted in Figure c, the removal efficiency of Fe(0)/Fe 3 C@MesoC to Cr­(VI) dropped to 36% after adding 1,10-phenanthroline, while adding tert -butanol had little effect on Fe(0)/Fe 3 C@MesoC for the reduction of Cr­(VI), and Fe(0)/Fe 3 C@MesoC still retained a 92% removal efficiency.…”
Section: Results and Discussionmentioning
confidence: 99%
“…NZVI, ferrous ions, and active H* are found to be the primary reductive species in the ZVI-based reduction process. 30,31 Therefore, it is necessary to examine their contribution to Cr(VI) reduction in the Fe(0)/ Fe 3 C@MesoC system. 1,10-Phenanthroline and tert-butyl alcohol were used as scavengers to quench the surface ferrous ions and H*, respectively.…”
Section: Electron Efficiencymentioning
confidence: 99%